PERANCANGAN FASILITAS KERJA AKTIVITAS PEMINDAHAN BATU BATA PADA UKM NGADIMAN - Febri, Febri Irawan Tanjung; hasibuan, Rizki (Computer Science and Industrial Engineering, 2022)
Ngadiman UKM which is located in the Barelang area is a small and medium business engaged in the manufacture of bricks. The activity of moving bricks from the printing process to the drying process is done manually and repeatedly. Based on the results of the Nordic Body Map questionnaire, the results showed that there were complaints on the neck, nape, back, waist, left forearm and right forearm, left wrist and right wrist and left and right hands. The result of the load value with NIOSH is 3,801 kg / LI > 1, indicating that the activity contains a risk of fatigue to spinal cord injury and corrective action. the typical obtaining a work risk score using REBA is 7 which is included in the moderate category and needs to be corrected. To attempt to lessen this danger , it is proposed to design a work facility in the form of an ergonomic brick removal trolley. The application of the proposed work facility design is obtained by the final calculation of NIOSH/LI < 1 with a value of 0.834 kg / LI < 1 indicating that the activity does not contain the risk of fatigue to spinal cord injury and belongs to the safe category, as well as the target specification for the moving brick trolley designed according to anthropometry. worker. Anthropometric data used in the design are Standing Elbow Height (TSB), Shoulder Width (LB), and Hand Grip (GT).